(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
People nowadays are looking for food that are easy to cook and ready to eat. Meat is one of the food Filipinos love toeat and they always include in the dish of every family. They are often the main dish in Filipinos gatherings. It was in this aspects that Meatinated aims to create and innovate the on meat products. The purpose of this business was to present to the target market the innovative flavors and varieties of the proposed product that can capture the taste of the consumers. The researchers conducted a food taste and survey at Barangay 171 Bagumbong, Caloocan City. The proponents prepared sample products and conducted a food taste among fifty (50) random individuals. Respondents were given questionnaires and answered freely according to the content of the questionnaires. The results reflected that the proponents’ proposed product has a big opportunity to be successful in the market. The different flavors of the product had a positive feedback from the target consumers of the business. The business proponents created a formal survey that included the demographic profile of the respondents and sets of questions that helped the proponents for data analysis. The idea of using folding fan and social media as an alternative marketing strategy can be very helpful for the study as a starting business. The proponents’ location for the business was good because it was surrounded by many suppliers and accessible to all customers. The proponents’ business product was new to the market although the root product was common. The researchers’ financial statement must be kept on increasing each year for return on investment within 5 years.